Impact of COVID-19 pandemic and lockdown among Men who have sex with Men living with HIV in Argentina (Actualizaciones en Sida e Infectología, 2021)
Background: People living with HIV (PLWH) are at increased risk of mental health complications. In order to mitigate the spread of COVID-19 in our country, an early quarantine was established. We studied the impact of COVID-19-related stress and quarantine in men who have sex with men living with HIV(MSMLH) in Argentina.Materials and methods: An anonymous survey was conducted between April and May 2020. PLWH in follow-up at a private institution in Argentina were included. We assessed adherence to preventive measures of COVID-19 and antiretroviral treatment, access to resources, psychosocial factors and substance use during quarantine. This analysis focused on MSMLH results.Results: Among 1336 participants included, 596 self-reported as MSMLH (median age 44, IQR 35-52). Quarantine adherence was 96.8%; household job loss 55.4%. Interruption to access to antiretroviral medication was observed in 4.9% and 29.9% reported suboptimal adherence. Mental health problems were common: depression (14.1%), loneliness (15.6%) anxiety (20.2%).Conclusions: Our study showed high adherence to preventive measures during the beginning of lockdown and difficulties to access health services. The COVID-19 pandemic has compromised the country's economy; this study shows its impact on MSMLH access to basic resources. Since MSMLH mental health has been affected, the pandemic highlights the need of a comprehensive approach to our patients' health.
Keywords: HIV; COVID-19; Argentina; mental health